Treatment of M. Meniere with Betahistine: Critical Remarks on the BEMED Study - Ernst, A.; Schlattmann, P.; Waldfahrer, F.; Westhofen, M. (Laryngo-Rhino-Otologie, 2017)
The BEMED study (BMJ 2016; 352: DOI 10.1136) was designed as multi-centric, double-blind, plaebo-controlled study in patients with Menière's disease. It should compare a low-level (2 × 24 mg/d) vs. high-level (3 × 48 mg/d) betahstine intake vs. placebo. The primary endpoint was the "number of vertigo attacks lasting longer than 20 min as documented in a patient's diary". The main finding of the study was that betahistine did not significantly better reduced the number of vertigo attacks than placebo. Therefore, the BEMED study should be critically discussed in the present paper.
EVALuna2:35530